2006
DOI: 10.1542/peds.2005-0785
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Fatality in Postdiarrheal Hemolytic Uremic Syndrome

Abstract: Diarrheal HUS patients presenting with oligoanuria, dehydration, WBC >20 x 10(9)/L, and hematocrit >23% are at substantial risk for fatal hemolytic uremic syndrome. Such individuals should be referred to pediatric tertiary care centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
1
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(110 citation statements)
references
References 26 publications
5
97
1
7
Order By: Relevance
“…One potential strength of this study is that we present data on a large number of consecutive patients from a single institution with inclusion criteria of referral for plasma exchange and a blood picture consistent with thrombotic microangiopathy (regardless of presumed underlying cause). Our patient population of 65 cases was comparable with that of other series published in the literature [20][21][22]. Our consistent approach over the years has previously allowed us to aid identification of significant predisposing factors to TMA [2].…”
Section: Discussionsupporting
confidence: 64%
“…One potential strength of this study is that we present data on a large number of consecutive patients from a single institution with inclusion criteria of referral for plasma exchange and a blood picture consistent with thrombotic microangiopathy (regardless of presumed underlying cause). Our patient population of 65 cases was comparable with that of other series published in the literature [20][21][22]. Our consistent approach over the years has previously allowed us to aid identification of significant predisposing factors to TMA [2].…”
Section: Discussionsupporting
confidence: 64%
“…Generally, the prognosis of STEC-HUS is favourable in the majority of children, although serious systemic complications, such as haemorrhagic colitis and CNS involvement, can occur and mortality is between 1% and 5% [40][41][42]. In patients aged over 65 years, a lethal outcome occurs in up to 50% of cases [43].…”
Section: Hus: Stec-hus and Ahusmentioning
confidence: 99%
“…In patients aged over 65 years, a lethal outcome occurs in up to 50% of cases [43]. Long-term consequences affect up to 20% of children with STEC-HUS and include arterial hypertension, neurological impairment, chronic kidney disease, or diabetes mellitus [40,41,44].…”
Section: Hus: Stec-hus and Ahusmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated a significant association between hemoconcentration and severe bowel injury, the need for and longer duration of dialysis, and acute phase death [1,2]. In their recent paper published in Pediatric Nephrology, Ardissino and colleagues found in a cohort of 61 patients that hemoconcentration at admission also correlated with major neurological involvement [3].…”
mentioning
confidence: 99%